O acesso ao benefício de prestação continuada (BPC) pela mediação do Juizado Especial Federal: uma experiência de alcance de direitos socioassistenciais - Pacheco, Solange (2010)
This study focuses on analyzing the Beneficio de Prestação Continuada da Assistencia Social (BPC), a cash transfer programme as set forth in the 1988 Brazilian Federal Constitution, the main provision of the Brazilian Social Assistance policy, aimed at elder and disable people. A highly relevant topic, as the Benefício de Prestação Continuada (BPC) grants a monthly income for elder and disable people, incapable of earning income for their own survival, or having it provided by their family. This study demonstrates the admission difficultness in the Benefício de Prestação Continuada (BPC), intending mostly on the regulating legislation s flaws put to practice on the benefit s administration. It also demonstrates the course of events of people that, after having the benefit denied, make a legal claim for it in the justice. Finally, It shows the increased right of admittance of the benefit, produced by judgmental sentences from the Federal Justice